A instalação e desenvolvimento de um Cluster comercial gerando diferencial competitivo: estudo de caso no setor da cadeia produtiva do algodão - Fracaroli, Fernando (2014)
This study aimed to examine whether on the administrative, technological and business reality installing a commercial cluster can generate a competitive advantage for organizations, which through the literature search and multicases was possible to conclude that when it comes to performance, market entry development and production, the creation and development of a commercial cluster becomes like a market strategy every day more in the Brazilian scenario. That was conclusive and exhaustive, random noticing gaps difficulties for greater profitability within a cluster, this excels when the participating organizations are smaller, devoid of preparation for the market, in that the cluster is a commercial real leverage. Compete and cooperate simultaneously making practical the concept of competition strategy that was many national companies have joined for working in the market today are concluding that this is a valid competitive strategy and still very much in vogue and grow in the country